Diagnóstico y propuesta de un manual de procesos y procedimientos para la unidad de control de bienes del gobierno autónomo descentralizado provincial de Pastaza, para el año 2015. - Villafuerte Hidalgo, Jessica Johana (2016)
This research has as a main purpose to propose a Process and Procedures Manual for Real Control Unit of the Autonomous Decentralized Provincial Government of Pastaza, 2015. Based on the analysis made it was possible to demonstrate structural flaws in different areas where there does not exist a planning based on the requests, which causes debts in the execution of the processes, that situation was observed in the elaboration of this work, that tool will allow to improve the administrative processes that are executed in the above mentioned Unit, for that reason the present proposal is born with the initiative to improve the management of Human Talent of the Public Entity, with the purpose that the personnel gets out of debt in an effective and efficient way in its work area. The methodology that was used for the development of the research was the deductive method, which allowed to diagnose the current situation of the organization for the collection of information, another method that was applied was the descriptive method already described the activities, functions, and times of the processes and procedures that are performed in the Property Control Unit As for realized analysis, there were demonstrated the processes executed in the existing areas, with the intention of evaluating the administrative situation of the organizational structure, consistently, the implementation of the manual to improve the control and administration of the goods that allow to diminish the times used in the delivery of the goods and services that gives the institution, both to the internal and external clients. Other considered aspects are orientated to establish the mechanisms that they allow to identify the useful time of life of the goods, the procedures to give them of low and later reinstatement, As the same way the needs to stablish mechanism of periodic update of the inventories of goods, fixed assets or fungibles goods as tool of a lot of importance in the administrative area. Equally the offer establishes the need to possess a process of reinstatement in case of loss or deterioration of goods, nowadays is not applied of opportune form for lack of the process and procedures manual. Also is demonstrated the need to have a computer system orientated to a better record of the goods, in each involved areas of this work, as the punctual need to implement a process, principally for the delivery of fuel and lubricants, thinking that those are submitted on the basis of the vehicle’s needs, without considering the realized work or the kilometer driven. Through this Manual will stablished guidelines and mechanisms that requires the institution to administrative level for the compliance of policies and regulations laid down in General rules for the administration, use and control of assets and inventories of the Public Sector, Structural and Functional Organic Regulation of GAD Pastaza Provincial and other regulations, defining the politics and/or norms that circumscribe the general frame of performance of the personnel. As strategy to reach the institutional aim " to modernize adequately his operations and services on the basis of the in force legislation and the process application of deconcentration and decentralization ", that sustains the administrative management of Pastaza's Provincial GAD. One recommends to implement the manual of processes and procedures, socializing it with the whole personnel of the institution, with the purpose as which it uses as guide for the execution of the processes that shape the manual, facilitating the daily work, the optimization of the time, the economic resources, the flow of information and the communication between the public servants of the Autonomous Decentralized Provincial Government of Pastaza.